THE RELATIONSHIP BETWEEN PROCEDURE AND SUPERVISION ON THE QUALITY OF MEDICAL RECORD IN IMELDA HOSPITAL - Zulham Andi Ritonga; Ida Yustina; Destanul Aulia (Alta Dharma Publisher, 2019)
The quality of a good medical record must meet the indicators of completeness and accuracy of filling, timeliness in safety and provision of medical records that meet legal requirements. The purpose of this study was to analyze the influence of procedures and supervision on the quality medical records for inpatient. This research is survey research with explanatory research design. The research was conducted at Imelda Hospital. The research population was 238 people and the sample was 100 people. The sampling technique is stratified random sampling which divides the population into homogeneous groups (strata) proportionally: 21 doctors, 65 nurses, and 14 medical records officers, from each stratum a random sample is taken. Data analysis using univariate, bivariate with the chi-square test, and multivariate using multiple logistic regression tests. The results showed that the procedure factor had no effect on the quality of medical records at the Imelda Hospital, p-value 0.520> 0.05. The controlling factor influences the quality of medical records at Imelda Hospital, p-value 0.001 <0.05. The hospital implements routine surveillance with evaluations every week, every month, every six months, and every year so that medical records become of high quality, that is, medical records are complete, accurate, returned on time, and meet legal requirements. Keywords: medical record quality of Inpatient Care, Supervision, Procedure